Research on Control Method for DC Voltage of Cascaded Multi-level STATCOM Based on Flying-capacitor - 孙乐; 岳小龙; 熊连松; 卓放 (Kongzhi Yu Xinxi Jishu)
Cascaded multilevel converter-based STATCOM is widely used in the high-power situations, but the DC-side voltage of modules in series is hard to balance, which seriously affects the compensation effect of the STATCOM. Therefore, it is very important for the technology application to maintain balance and stability of DC-side voltage of each module. In this paper, we first describes the basic structure of STATCOM, reactive power compensation principle and control algorithms briefly. Then, drawing lessons from the existing hardware and software control method for reference, we propose a new method to control the DC voltage by using an additional flying-capacitor. Compared with the traditional hardware control method, we use fewer devices. Compared with the traditional software control method, our control is less complex. At last, we use cascaded two modules five-level STATCOM as an example for simulation. The results show that the method we proposed can accomplish the DC voltage balance and stability.